with the assistance of A. D. Syrokomla-Stefanowska, Proceedings of the 28th International Congress of Orientalists, Camberra 1971 (1976)
Sumerian and Akkadian: 49-51; Iranian: 51-54; Phoenician and Ugaritic: 54-57 (summaries).